PERANAN PAJAK PARKIR DAN RETRIBUSI PARKIR DAN RETRIBUSI PASAR TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA SEMARANG (Students' Journal of Accounting and Banking, 2014)
This study was conducted to analyze the role of parking tax, parking levies, and levies on Revenue Market. The study object is the city of Semarang by using secondary data time series period 2002-2011.The data analysis technique used is multiple linear regression equation least squares and hypothesis testing using the t-statistic for testing the partial regression coefficients with a significance level of 5%. During the observation period of the study show that the data are normally distributed. Based test for normality, multicollinearity test, test and test heteroskedastisidas autocorrelation in the classical assumption that the variable was not found to deviate. This shows the available data has been qualified using multiple linear regression models.Results of this study indicate that the parking tax and levies variable market showed a positive and significant role of the Revenue. While variable parking fees has a negative and significant coefficient value indicate that no optimal role to change the original income. This is due to the parking levy receipts during the year of observation has not been optimal. Keywords: Regional Revenue, Parking Tax, Parking Levy, and Levy Market